Comparison of Impedance Measurements in a DSP using Ellipse-fit and Seven-Parameter Sine-fit Algorithms - Ramos, Pedro M. (2010)
In this paper, two DSP implemented algorithms for impedance measurements are compared. Previously published results demonstrate the usefulness of sine-fit algorithms and ellipse-fit algorithms for impedance measurements where two channels are simultaneously acquired with analog to digital converters. The comparison between the two implemented algorithms is done by analyzing the average execution time, memory requirements and experimental standard deviation of the estimated impedance parameters. For the first time, the seven-parameter sine-fit algorithm is adapted so that it does not need the construction and manipulation of its largest matrix thus requiring less overall memory. This improvement can be used to acquire and process more samples (leading to reduced experimental standard deviations of the estimated parameters) with the same memory size.